1987
DOI: 10.1002/1097-0142(19871015)60:8<1842::aid-cncr2820600828>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Observations of serum trace elements in chronic lymphocytic leukemia

Abstract: Serum trace elements (STE) were measured in 50 patients with chronic lymphocytic leukemia (CLL) and 100 normal subjects. Copper was higher in patients than in controls (1.50 +/- 0.06 versus 1.10 +/- 0.02 micrograms/ml, P less than 0.001), increased steadily from Stage 0 to Stage 4 (P = 0.002), and correlated with the lymphocyte count and serum lactate dehydrogenase (P less than 0.01) but not with acute phase reactants. Zinc was lower in patients than in controls (0.94 +/- 0.03 versus 1.10 +/- 0.02 micrograms/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…In agreement with observations in patients with cancer and other diseases[181920] but unlike what was found in a group of patients with reticuloendothelial tumors. [21] A direct association between albumin and serum selenium levels might be explained by nutritional factors or by the fact that albumin represents a selenium-containing protein,[22] it seems appropriate to examine the possible utility of determining selenium status in the clinical evaluation of patients with lymphoid malignancies.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with observations in patients with cancer and other diseases[181920] but unlike what was found in a group of patients with reticuloendothelial tumors. [21] A direct association between albumin and serum selenium levels might be explained by nutritional factors or by the fact that albumin represents a selenium-containing protein,[22] it seems appropriate to examine the possible utility of determining selenium status in the clinical evaluation of patients with lymphoid malignancies.…”
Section: Discussionsupporting
confidence: 92%
“…Over half of the patients in the study with newly diagnosed AML or HL, and 26% of those with FL, had a selenium concentration that would be considered low in the UK. The low serum selenium in these patients confirmed the same observation in our previous study in aggressive B‐cell lymphomas (Last et al , 2003) and other smaller studies in CLL (Beguin et al , 1987), AML (Beguin et al , 1989) and lymphoma (Avanzini et al , 1995).…”
Section: Discussionsupporting
confidence: 90%
“…In our own study there was a significant negative correlation between white cell count and selenium concentration ( P = 0·0003) in AML patients, and selenium and disease stage in HL ( P = 0·002). Other reports have described a similar negative correlation between serum selenium and lymphocyte count in CLL (Beguin et al , 1987) peripheral blast cell count in AML (Beguin et al , 1989) and disease stage in lymphomas (Avanzini et al , 1995), suggesting that utilization of selenium by the tumour may decrease serum selenium levels and act as a surrogate for bulk of disease.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Vitamin K de®ciency (Carlin & Walker, 1991), vitamin B 12 de®ciency (Milligan et al, 1987), thiamin de®ciency (Rovelli et al, 1990) and magnesium depletion (June et al, 1985), have all been reported to occur in adult patients following BMT. Similarly, biochemical zinc and copper de®ciencies have been reported in children with leukaemia (Beguin et al, 1985(Beguin et al, , 1987 and solid tumours (Hrgovcic et al, 1986), and also in children with thalassaemia receiving desferrioxamine (Uysal et al, 1993). Decreased intake and absorption, and increased intestinal or urinary losses were some of the mechanisms of these de®ciencies.…”
Section: Micronutrient De®cienciesmentioning
confidence: 74%